CARDIOVASCULAR RESPONSE IN MID AND LONG-DISTANCE RUNNERS UNDER TRAINING - Zhang,Yinfu (2022)
ABSTRACT Introduction: Research on the effects of exercise on the cardiovascular system has a long history that has recently been expanded with echocardiography. Research using Doppler echocardiography has been increasing because of the safe and non-invasive method of examination to study cardiac morphology and function. However, few studies on functional cardiac changes in mid and long-distance runners under training are still few. Objective: Study the monitoring of cardiovascular response in middle and long-distance runners during training. Methods: The CFOCS-I cardiovascular function detector was used to observe 24 indices of cardiac pump function, vascular function, and microcirculation in 12 female middle-distance runners. Results: According to the test results, diastolic force, systolic force, systolic function, left ventricular ejection fraction increased during the proposed loading exercise. The mean systolic and mean pulse pressures increased significantly with exercise load (P<0.01). Conclusion: Mid and long-distance runners demonstrated significant cardiac changes in ventricular shape, size, and systolic function, accompanied by significant changes in diastolic function when subjected to intense exercise. Evidence Level II; Therapeutic Studies - Investigating the result.